A high-pressure resistant ternary network hydrogel based flexible strain sensor with a uniaxially oriented porous structure toward gait detection. Issue 48 (25th November 2022) - Dong, Xin; Ge, Yaqing; Li, Keyi; Li, Xinyi; Liu, Yong; Xu, Dongyu; Wang, Shoude; Gu, Xiangling
Abstract : The interaction between triple networks in hydrogel and the flexible sensor prepared are applied to gait detection. Abstract : Gait abnormalities have been widely investigated in the diagnosis and treatment of neurodegenerative diseases. However, it is still a great challenge to achieve a comfortable, convenient, sensitive and high-pressure resistant flexible gait detection sensor for real-time health monitoring. In this work, a polyaniline (PANI)@(polyacrylic acid (PAA)–polyvinyl alcohol (PVA)) (PANI@(PVA–PAA)) ternary network hydrogel with a uniaxially oriented porous featured structure was successfully prepared using a simple freeze–thaw method and in situ polymerization. The PANI@(PVA–PAA) hydrogel shows excellent compressive mechanical properties (423.44 kPa), favorable conductivity (2.02 S m −1 ) and remarkable durability (500 loading–unloading cycle), and can sensitively detect the effect of pressure with a fast response time (200 ms). The PANI@(PVA–PAA) hydrogel assembled into a flexible sensor can effectively identify the movement state of the shoulder, knee and even the sole of the plantar for gait detection. The uniaxially oriented porous structure enables the hydrogel-based sensor to have a high rate of change in the longitudinal direction and can effectively distinguish various gaits. The construction of a hydrogen bond between PANI and the PVA–PAA hydrogel ensures the uniform distribution of PANI in the hydrogel to form a ternary network structure, which improves the pressure resistance and conductivity of the PANI@(PVA–PAA) hydrogel. Thus, PANI@(PVA–PAA) hydrogel flexible sensor for gait detection can not only effectively monitor some serious diseases but also detect some unscientific exercise in people's daily life.